Mechanical Behavior of Medium Carbon Steel welded with SMAW And Corroded with Sea Water - Diah Kusuma Pratiwi; Rasyidi Rasyidi (Journal of Mechanical Science and Engineering, 2015)
The problem of Â metal corrosion is a very serious to be observed, especially the corrosion of medium carbon steel because it can reduce the economic value of the metal. Corrosion of carbon steel is influenced by the environmental conditions. This paper discusses the effect of the corrosion rate of medium carbon steel with SMAW welding and corrodes it with sea water during several hour. Electrodes of AWS A5.1E7016 type were used in the welding. The test results show that the medium carbon steel which was corroded with sea water has small weight loss. It seem that the weight loss has small influence on the mechanical behavior of the metal. For the welded medium carbon steel, the ultimate strength and surface hardness are smaller than the un-welded one. The microstructure of welded medium carbon steel has unsimilar structure with un-welded steel because it has about the same amount of ferlite, ferrite and martensite.